IMPLEMENTATION OF A SMART EMERGENCY LAMP HOME PROTOTYPE BASED ON INTERNET OF THINGS (IoT) USING NODEMCU ESP32 MICROCONTROLLER - Muhammad Fajri; Bustami Bustami; Lidya Rosnita (RADJA PUBLIKA, 2024)
Power outages in residential environments such as boarding houses often disrupt safety and comfort due to the lack of adequate emergency lighting systems. This study aims to develop a Smart Emergency Lamp Home prototype using the Internet of Things (IoT) with a NodeMCU ESP32 microcontroller. The system is designed to automatically activate emergency lighting during power failures and enable real-time monitoring and control via a web-based interface. The research follows an engineering method involving system design, hardware-software integration, and prototype testing. The hardware includes power sensors (INA219 and PZEM-004T), a 12V battery, inverter, relay module, and TFT display, while the software uses Node.js and a PostgreSQL database for web monitoring. Testing results demonstrate the system's high responsiveness, accurate sensor data transmission, efficient power usage (with power factors above 0.94), and stable operation during simulated blackouts. The notification system also worked effectively, providing timely alerts regarding lamp status and battery conditions. This prototype offers a practical, scalable, and low-cost solution for emergency lighting in residential settings and can be further developed with features like solar charging and mobile-based monitoring.